Pulmonary adiaspiromycosis in critically endangered northern hairy‐nosed wombats (Lasiorhinus krefftii). Issue 11 (27th October 2017) - Schaffer‐White, AB; Harper, D; Mayhew, M; McKinnon, A; Knott, L; Allavena, RE
Abstract : Background: The northern hairy‐nosed wombat ( Lasiorhinus krefftii ) is critically endangered, with only 200 individuals remaining in the wild. Individuals are rarely available for detailed pathological assessment and identification of disease threats to individuals is critically important to species conservation. Case report: Two male northern hairy‐nosed wombats, part of the Richard Underwood Nature Refuge population, were presented for necropsy, 5 months apart. They were found to have succumbed to adiaspiromycosis caused by the fungus Emmonsia parva . Pathological presentations were of severe pulmonary oedema and fibrosis, and pleuritis, respectively. Characteristic fungal adiaspores were noted on histopathological examination. The wombats had concurrent variably severe ectoparasite and endoparasite burdens. Conclusion: These are the first reported cases of adiaspiromycosis in northern hairy‐nosed wombats and the organism was associated with significant pathological changes. The rarity and the logistical challenges of presenting northern hairy‐nosed wombats for pathological assessment are a challenge to identifying disease threats in this critically endangered species.